Arrangement of ICC Authorities Based on the 1998 Rome Statute - Mubarak, Ridho; Nadira, Cici (Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to investigate the regulation of the authority of the International Criminal Court (ICC) based on the 1998 Rome Statute. The main focus of the research is to analyze the structure and scope of the ICC's authority, as well as its impact on international law enforcement. Another objective is to evaluate the effectiveness of the mechanisms and procedures established in the Rome Statute to deal with violations of international crimes. The research methodology uses a juridical-normative approach by analyzing the text of the Rome Statute, conventions, and related legal literature. In addition, case studies of cases that have been tried by the ICC are also used to gain a practical understanding of the implementation of such authority. The results show that the Rome Statute authorizes the ICC to pursue individuals who commit war crimes, crimes against humanity, the crime of genocide, and the crime of aggression. However, the research identifies several challenges in the implementation of these powers, including issues of sustainability, international cooperation, and inequality in the prosecution process. This research has significant implications for understanding and improving the international criminal justice system. Policy recommendations can be made to strengthen the ICC's powers, enhance international cooperation, and ensure fairness and continuity in the prosecution of international criminals. As such, this research can make an important contribution to the development of a more effective and just international legal system.